The Effect of Management and Internal Audit Inspectorate on the Effectiveness of Internal Controls on the Procurement of Goods and Services for the Government of West Papua Province - Kaleb Yohana Karubaba️ (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract This study aims to analyze the influence of management and internal audit inspectorate partially and simultaneously on the effectiveness of internal control over the procurement of goods and services of the Government of West Papua Province. This study uses a quantitative approach, a sample of 40 people with a saturated sample technique, data collection by questionnaire, and using multiple linear regression analysis. The results showed that the management and internal audit inspectorate had a positive and significant partial and simultaneous effect on the effectiveness of internal control over the procurement of goods and services in West Papua Province. Calculation of the coefficient of determination (R2) results in 0.607, which means that 60.7% of the dependent variable (effectiveness of internal control) can be explained by the independent variable (management and internal audit inspectorate), while the remaining 39.3% is explained by other variables outside the research model. this. Keywords: Management, Internal Audit, Control Effectiveness, Goods and Services.